Extracellular 4'-phosphopantetheine is a source for intracellular coenzyme A synthesis. - Srinivasan, B.; Baratashvili, M.; van der Zwaag, M.; Kanon, B.; Colombelli, C.; Lambrechts, R.A.; Schaap, O.; Nollen, E.A.; Podgorek, A.; Kosec, G.; Petkovi?, H.; Hayflick, S.; et al. (Nature Chemical Biology, 2015)
The metabolic cofactor coenzyme A (CoA) gained renewed attention because of its roles in neurodegeneration, protein acetylation, autophagy and signal transduction. The long-standing dogma is that eukaryotic cells obtain CoA exclusively via the uptake of extracellular precursors, especially vitamin B5, which is intracellularly converted through five conserved enzymatic reactions into CoA. This study demonstrates an alternative mechanism that allows cells and organisms to adjust intracellular CoA levels by using exogenous CoA. Here CoA was hydrolyzed extracellularly by ectonucleotide pyrophosphatases to 4'-phosphopantetheine, a biologically stable molecule able to translocate through membranes via passive diffusion. Inside the cell, 4'-phosphopantetheine was enzymatically converted back to CoA by the bifunctional enzyme CoA synthase. Phenotypes induced by intracellular CoA deprivation were reversed when exogenous CoA was provided. Our findings answer long-standing questions in fundamental cell biology and have major implications for the understanding of CoA-related diseases and therapies.